Duration and magnitude of the postoperative risk of venous thromboembolism in middle aged women: prospective cohort study. - Sweetland, S; Green, J; Liu, B; Berrington de González, A; Canonico, M; Reeves, G; Beral, V (2009)
OBJECTIVE: To examine the duration and magnitude of increased risk of venous thromboembolism after different types of surgery. DESIGN: Prospective cohort study (Million Women Study). SETTING: Questionnaire data from the Million Women Study linked with hospital admission and death records. PARTICIPANTS: 947 454 middle aged women in the United Kingdom recruited in 1996-2001 and followed by record linkage to routinely collected NHS data on hospital admissions and deaths. During follow-up 239 614 admissions were for surgery; 5419 women were admitted, and a further 270 died, from venous thromboembolism. MAIN OUTCOME MEASURES: Adjusted relative risks and standardised incidence rates for hospital admission or death from venous thromboembolism (pulmonary embolism or deep vein thrombosis), by time since and type of surgery. RESULTS: Compared with not having surgery, women were 70 times more likely to be admitted with venous thromboembolism in the first six weeks after an inpatient operation (relative risk 69.1, 95% confidence interval 63.1 to 75.6) and 10 times more likely after a day case operation (9.6, 8.0 to 11.5). The risks were lower but still substantially increased 7-12 weeks after surgery (19.6, 16.6 to 23.1 and 5.5, 4.3 to 7.0, respectively). This pattern of risk was similar for pulmonary embolism (n=2487) and deep venous thrombosis (n=3529). The postoperative risks of venous thromboembolism varied considerably by surgery type, with highest relative risks after inpatient surgery for hip or knee replacement and for cancer-1-6 weeks after surgery the relative risks were, respectively, 220.6 (187.8 to 259.2) and 91.6 (73.9 to 113.4). CONCLUSION: The risk of deep vein thrombosis and pulmonary embolism after surgery is substantially increased in the first 12 postoperative weeks, and varies considerably by type of surgery. An estimated 1 in 140 middle aged women undergoing inpatient surgery in the UK will be admitted with venous thromboembolism during the 12 weeks after surgery (1 in 45 after hip or knee replacement and 1 in 85 after surgery for cancer), compared with 1 in 815 after day case surgery and only 1 in 6200 women during a 12 week period without surgery.